Associação de Futebol Popular do Concelho de Espinho - Promoção e desenvolvimento do futebol em Espinho - Marco Paulo da Silva Ferreira (2016)
The Associação de Futebol Popular do Concelho de Espinho (Popular Football Association) is a non - profit sports organization whose aim is to organize amateur football matches for senior males citizens. This study aimed to analyse sports management at AFPCE which has been promoting sports events since 1983. By consulting the relevant documents the beginning of its activity has been set out, the entity of the four sport seasons, from 2012 to 2016, characterised and the importance of the associative sports official engaged in activities at AFPCE on a voluntary basis described. Thus, the methodology used for collecting information was the interviews made to the governing bodies - the Chairman of the Council of Clubs, Chairman of the Board, Chairman of the Supervisory Board and Chairman of the Arbitration Board. Furthermore, the documents of the organization of our study were also analysed. The main results show that the AFPCE is a non-profit organisation; promotes senior male football matches; involves around 1000 sports agents; 27 clubs participate in the its matches; that it is dependent on public funding; fulfils the management demands; all the Sports Agents are volunteers, and do not have any training in the field; it has been concluded that it is a financially stable and organized association.